2020
DOI: 10.1021/acscentsci.9b01121
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mitochondrially Targeted Nanoconstructs to Neoadjuvant X-ray-Induced Photodynamic Therapy for Rectal Cancer

Abstract: In this work, we brought together two existing clinical techniques used in cancer treatmentX-ray radiation and photodynamic therapy (PDT), whose combination termed X-PDT uniquely allows PDT to be therapeutically effective in deep tissue. To this end, we developed mitochondrially targeted biodegradable polymer poly(lactic-co-glycolic acid) nanocarriers incorporating a photosensitizer verteporfin, ultrasmall (2−5 nm) gold nanoparticles as radiation enhancers, and triphenylphosphonium acting as the mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 43 publications
(66 reference statements)
0
54
0
Order By: Relevance
“…In addition to the cytotoxic action of ROS on blood vessels, PDT directly affects cancer cells by destabilization of cell membranes, enhancement of autophagy and apoptosis [ 27 ]. The efficiency of VP-aided PDT was demonstrated in various experimental models of mammary carcinoma [ 28 , 29 ], pancreatic [ 30 ] and colorectal [ 23 , 31 , 32 ] cancers, glioblastoma [ 33 ] and some other malignancies (see references in [ 34 ]). Clinical application of VP for PDT was reported for the eye, pancreatic and skin cancer [ 1 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the cytotoxic action of ROS on blood vessels, PDT directly affects cancer cells by destabilization of cell membranes, enhancement of autophagy and apoptosis [ 27 ]. The efficiency of VP-aided PDT was demonstrated in various experimental models of mammary carcinoma [ 28 , 29 ], pancreatic [ 30 ] and colorectal [ 23 , 31 , 32 ] cancers, glioblastoma [ 33 ] and some other malignancies (see references in [ 34 ]). Clinical application of VP for PDT was reported for the eye, pancreatic and skin cancer [ 1 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of VP was especially strongly motivated by our own recent results indicating a novel mechanism of light-independent triggering of PS activity of VP by clinically relevant dose of X-rays [ 19 , 23 , 31 , 32 ]. Shifting from the visible light to X-rays as initiators of ROS generation (such as PDT to RDT), allows to overcome the tissue penetration depth limit of conventional PDT [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al proposed a platform using PLGA vesicles to carry PS verteporfin and gold NPs (2–5 nm) together for efficient energy transfer between the PS and Au NPs. The NPs showed excellent results in PDT with a low dose of radiation (4 Gy) [ 53 ]. PS-modified α-Zn 2 SiO 4 -doped silica NPs were also used to emit X-ray-excited optical luminescence (XEOL).…”
Section: Innovative Nanotechnologies To Improve Pdt Treatmentsmentioning
confidence: 99%
“…Similarly, other investigators have shown that verteporfin with 690 nm laser irradiation induced specific and severe damage to the mitochondrial membrane in astrocytes with elevated mROS generation [ 26 ]. PDT with verteporfin has been effective in various types of cancers such as gastric cancer, rectal cancer, and breast cancer [ 154 , 155 , 156 ]. Intracellular ROS production plays a crucial role in the anticancer effects of second-generation photosensitizers and its safety has been investigated in various types of malignant tumors [ 149 , 157 , 158 , 159 , 160 ].…”
Section: Photodynamic Therapymentioning
confidence: 99%